2009
DOI: 10.1111/j.1365-3016.2008.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and reproductive wastage in the Palestinian Territories

Abstract: Many studies have found that consanguinity poses a threat to child mortality and health and can also pose a threat to offspring survival before birth. However, there are conflicting findings with some studies having found no increased risk on offspring survival associated with consanguinity. Data from a population-based survey conducted in 2004 in the Palestinian Territories was used to assess the risk of consanguinity on offspring survival. The analysis was conducted on 4418 women aged 15-49 who were asked wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
1
20
2
Order By: Relevance
“…Consistent with previous studies conducted in developing countries, from rural Bangladesh to Uganda [10,11,33,34], this study showed that stillbirth rates were higher among mothers with no formal education compared to educated mothers. A study conducted in Norway indicated that stillbirth rates were higher in Norwegian women with fewer years of education, but not among Pakistani immigrant women in Norway [24].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies conducted in developing countries, from rural Bangladesh to Uganda [10,11,33,34], this study showed that stillbirth rates were higher among mothers with no formal education compared to educated mothers. A study conducted in Norway indicated that stillbirth rates were higher in Norwegian women with fewer years of education, but not among Pakistani immigrant women in Norway [24].…”
Section: Discussionsupporting
confidence: 91%
“…However, the results are divergent. Many studies have demonstrated that consanguineous marriages are associated with higher risk of autosomal recessive diseases and congenital malformations, mental retardation, higher pre-reproductive deaths, low birth weight and higher postnatal mortality among offspring (Khoury et al 1987;Khlat 1988;Bittles and Neel 1994;Bundey and Alam 1995;Stoltenberg et al 1999;Mokhtar and Abdel-Fattah 2001;Bener and Hussain 2006;Saadat 2007;Assaf et al 2008), whilst others fail to discover any association (Rao and Inbaraj 1977;Devi et al 1981;Reddy 1983;Al-Awadi et al 1986;Mumtaz et al 2007;Bittles and Black 2010;Gowri et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of consanguinity in Qatar is 54% [14]. Consanguinity has a known association with preterm births [15], as well as with perinatal wastage [16]. In our study, 35% of babies with congenital anomalies had declared futility on antenatal ultrasound scan.…”
Section: Resultsmentioning
confidence: 47%